The impact of ICT utilization to improve the learning outcome: A meta-analysis - Janu Arlinwibowo; Heri Retnawati; Badrun Kartowagiran (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study aimed to describe the impact of the utilization of technology on learning outcomes through a meta-analysis. Data was collected by documenting research that is resulted from various sources collected through internet. These articles were published from 2006 to 2019, in United Nations Language. The article discusses the influence of information and communication technology (ICT) on learning achievement, analyzed qualitatively, describing the data in the form of sample size, standard deviation, and average, and published in journals indexed in Google Scholar. The analysis design employed a contrast group with the random effect model that the effect size is corrected. The analysis was used JASP software for calculating the average aggregate difference, drawing a forest plot, and publication bias. The results of the analysis show that there is a significant difference between groups using ICT and non-ICT in the learning process (SE=1.13), groups of students who utilizing ICT in the learning have better learning outcomes than those who do not use ICT. Based on the results of the analysis, it is very clear the urgency of implementing ICT in supporting the learning process. Schools should conduct an assessment of the condition of the school and students and then choose the appropriate ICT implementation. Thus, the quality of the learning process and students' technological literacy improve.